Analysis of Improvements to Bank Capacitor Requirements in 20kv Voltage Distribution Network Panels for Power Plant 2 at PT. Toyota Motor Manufacturing Indonesia - Maria Ulfa; Lela Nurpulaela (Universitas Muhammadiyah Gresik, 2024)
This research aims to describe and analyze the effectiveness of using capacitor bank capacity in PT's power plant 2 distribution system. TMMIN. The focus is to analyze the initial design of capacitor bank requirements for each panel in the substation production line, including Painting, Assembly and Welding, to increase capacitor bank requirements according to electrical theory standards. The Power Factor calculation method is used to measure the required capacitor bank capacity. The power factor is influenced by the type of electrical load which is resistive, inductive or capacitive, with a value range between 0 and 1. A power factor close to 1 indicates high active power and better electrical power quality, while a power factor close to 0 indicates high reactive power. reducing power quality and increasing electrical energy use. The current power factor value is obtained from the actual voltage and active power conditions, and the required capacitor bank value is calculated with a target power factor of 0.9 or 0.95. According to calculations, the panels that can be repaired are panels 3, 4, 5, 6 Painting, panel 1 Assembly, and panel 1 Welding. The results show that 2 MDB panels reach ideal conditions with 6 steps of 2x50kVAR capacitor bank, while the other 6 MDB panels require an additional 2 steps of 2x50kVAR capacitor bank to achieve ideal conditions.